Reading Ashabul Kahfi in Relation to #KaburAjaDulu: Fazlur Rahman’s Double Movement and the Ethics of Withdrawal - Rosyawaly, Falika Nahwa; Ghianovan, Jaka; Mualim, Mohamad (Substantia: Jurnal Ilmu-Ilmu Ushuluddin, 2026)
This study examines the story of Ashabul Kahfi in Qur’an, Surah al-Kahfi 18:9–26, through Fazlur Rahman’s Double Movement approach in order to formulate an ethical reading of ‘uzlah (withdrawal or seclusion) in relation to the contemporary Indonesian hashtag #KaburAjaDulu (roughly, “just leave first”). The study employs a qualitative library research design with a conceptual-hermeneutic orientation. Its primary sources include the Qur’anic text, classical and contemporary Qur’anic commentaries, particularly Tafsir Ibn Kathir and M. Quraish Shihab’s Tafsir al-Misbah, and scholarly works on Rahman’s hermeneutics. Secondary sources consist of academic discussions on #KaburAjaDulu as a digital discourse. The analysis proceeds in two stages: first, by examining the socio-historical context of the Qur’anic narrative, and second, by identifying its ideal-moral principles and considering their relevance to contemporary social unease. The study finds that ‘uzlah in the story of Ashabul Kahfi is ethically meaningful when it emerges as a last resort under severe pressure, after moral deliberation, and for the preservation of faith and integrity. In contrast, #KaburAjaDulu should be read as a fluid digital discourse that may express frustration, critique, satire, or migration aspirations. The article argues that the story of Ashabul Kahfi offers ethical criteria for assessing discourses of “leaving,” without turning the hashtag into a direct equivalent of Qur’anic ‘uzlah.